System Restructuring, Value Expansion, and New Challenges: AI Era Journalism Practice Transformation and Challenges - Pan, Liangyu (International Journal of Social Sciences and Public Administration, 2024)
In the era of new media, the news industry is undergoing unprecedented changes, especially with the rapid development of AI in content generation (AIGC) technology, leading to significant transformations in the process and form of news production. This paper explores the application of AIGC technology in news production and its impact on user experience: the integration of AI technology not only enhances the efficiency and diversity of news production but also provides users with a more personalized and immersive news experience; however, this technological application also poses challenges for news workers, news audiences, and management. The aim of this paper is to elucidate the transformation of news production in the era of new media, discussing how to effectively utilize AIGC technology in the context of media convergence to promote the healthy development of the news industry.